Comparison of air pollution and the prevalence of allergy-related diseases in Incheon and Jeju City - Su Ho Jeong; Jeong Hee Kim; Byong Kwan Son; Seong Chul Hong; Su Young Kim; Geun Hwa Lee; Dae Hyun Lim (Korean Pediatric Society, 2011)
PurposeA high level of air pollutants can increase the number of patients with allergy-related diseases such as asthma and allergic rhinitis (AR). To analyze the association between air pollution and allergic disease, we investigated 2 areas in Korea: Incheon, an industrial area, and Jeju, a non-industrialized area.MethodsSecond grade students at elementary schools (11 schools in Incheon and 45 schools in Jeju) were examined in a cross-sectional study. A questionnaire was used and a skin prick test was performed. The levels of NO2, CO2, O3, particulate matter (PM) PM10/2.5, formaldehyde, tVOCs, and dust mites in the classrooms and grounds were determined.ResultsThe levels of outdoor CO, PM10, and PM2.5 were significantly higher in Incheon (P<0.01). The levels of indoor CO, CO2, PM10, PM2.5 were significantly higher in Incheon (P<0.01). The prevalence rates of AR symptoms at any time, AR symptoms during the last 12 months, diagnosis of rhinitis at any time, and AR treatment during the last 12 months were significantly higher in Incheon (P<0.01). The prevalence rate of wheezing or whistling at any time, and wheezing during the last 12 months were significantly higher in Incheon (P<0.01).ConclusionWe found that the children living in Incheon, which was more polluted than Jeju, had a higher rate of AR and asthma symptoms compared to children in Jeju. To determine the effect of air pollution on the development of the AR and asthma, further studies are needed.